Placenta accreta: Elective versus emergent delivery as a major predictor of blood loss - Seoud, M.A.; Nasr, R.; Berjawi, G.A.; Zaatari, G.S.; Seoud, T.M.; Shatila, A.S.; Mirza, F.G. (Journal of neonatal-perinatal medicine, 2017)
OBJECTIVE: To compare blood loss and the use for blood transfusion between elective (planned) and emergent cesarean hysterectomy performed for placenta accreta by a single, multidisciplinary team and to present the team’s pre-operative evaluation and the surgical technique. STUDY DESIGN: Prospective cohort study at a single tertiary care center. Maternal and neonatal outcomes were compared between elective and emergent delivery of pregnancies complicated by placenta accreta. The primary outcomes were the need for blood transfusion and the number of units transfused. RESULTS: A total of 28 cases of confirmed placenta accreta underwent peripartum hysterectomy, including 22 as elective and 6 as emergent. Eleven out of 22 (50%) subjects in the elective group received blood transfusion, while all subjects in the emergency group required transfusion (p = 0.03). More importantly, the number of units of packed red blood cells transfused was only 1.90 (±2.20) units in the elective cases compared to 7.83 (±4.90) units in cases performed emergently (p = 0.03). CONCLUSION: Elective cesarean hysterectomy for this indication using a clearly outlined surgical approach is associated with significantly lower blood loss and hence less need for transfusion, compared to its emergent counterpart.